2006
DOI: 10.1111/j.1365-3156.2006.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumsporozoite protein gene diversity among temperate and tropical Plasmodium vivax isolates from Iran

Abstract: SummaryTo date, there is no information on the genetic diversity of the circumsporozoite protein (CSP), a leading vaccine candidate, in Plasmodium vivax populations circulating in Iran. The gene for this protein, Pvcsp, was amplified from 374 P. vivax isolates collected in the temperate northern, and in the tropical southern endemic areas. PCR-RFLP analysis of the repeated central region revealed that the parasites collected in the northern area were almost exclusively of the VK210 type. Parasites collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
10
47
1
1
Order By: Relevance
“…Finally, 16 aa found in 12 of the Colombian isolates had also been reported for the P30 isolated (AY632258) in Iran. 10 The origin of the repeats could be the result of meiotic recombination that occurs during the diploid phase of the malaria life cycle. 9 Genetic mechanisms such as slipped-strand mispairing, 27 recombination, and gene conversion can be inferred from the formation and separation of such mutations, 28 including expansion or reduction of repeat sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 16 aa found in 12 of the Colombian isolates had also been reported for the P30 isolated (AY632258) in Iran. 10 The origin of the repeats could be the result of meiotic recombination that occurs during the diploid phase of the malaria life cycle. 9 Genetic mechanisms such as slipped-strand mispairing, 27 recombination, and gene conversion can be inferred from the formation and separation of such mutations, 28 including expansion or reduction of repeat sequences.…”
Section: Discussionmentioning
confidence: 99%
“…9 Both nonapeptides sequences are repeated ~20 times in their corresponding proteins; however, there is extensive polymorphism with regard to the number of repeats. 10 It has been shown that the prevalent phenotype of the P. vivax parasite in the study sites of Colombia is VK247 (59.7%), whereas VK210 accounts for one-third of the cases 32.8%; the remaining 7.5% corresponds to mixed infection. 11 Although previous nucleotide sequence analyses of the flanking regions (3′NR and 5′NR) of P. vivax CS protein have shown high conservation of these regions, recent studies indicated that isolates from Iran, Philippines, China, Brazil, and Korea contained previously undescribed point mutations and an insertion at the beginning of the 3′NR region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 All PvCSP variant genotypes have a worldwide distribution. 12,13 We conducted the present study to analyze sequences of these two genes from isolates obtained during 1999-2007 and to identify changes in the genetic diversity of the reemerged P. vivax population in South Korea. This study surveyed previous prevalence and evaluated current prevalence and is useful because it might predict future prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…This CSP gene sequence is similar to that of P. simiovale, a monkey malaria parasite originally found in Macaca sinica in Sri Lanka (Qari et al 1993a). All CSP variant genotypes have a worldwide distribution (Kain et al 1992, Gonzáles et al 2001, Imwong et al 2005, Zakeri et al 2006.…”
Section: Cspmentioning
confidence: 99%